Strategic development of Islamic religious educators in enhancing the pedagogical excellence of junior high school teachers - Mappanyompa, Mappanyompa; Rukimin, Rukimin; Saprun, Saprun; Sahwan, Sahwan (Jurnal Inovasi Teknologi Pendidikan, 2025)
Improving the professional competence of educators is crucial in enhancing the quality of education. However, many educational institutions still face challenges in consistently implementing development strategies, especially in integrating pedagogical, technological, and managerial skills to meet global demands. This study aims to explore educator development strategies to improve professional competence at Bani Hasyim Islamic Junior High School, Singosari, Malang. Using a qualitative descriptive method, data were collected through interviews with the school principal, three vice principals, the head of the national exam committee, and teachers of Indonesian, English, Arabic, and Islamic Religious Education. Data were analyzed using Miles and Huberman’s interactive model, which includes data collection, condensation, display, and conclusion drawing. The findings reveal three key strategies: (1) Educational Strategy, offering free higher education for teachers; (2) Training Strategy, structured in three levels-Level I for new teachers, Level II for quality improvement, and Level III for prospective vice principals; and (3) Responsibility Internalization Strategy, aimed at building a professional attitude and commitment. These strategies are expected to enhance curriculum relevance, learning quality, and educator readiness in facing global educational challenges. Future research should expand the scope to other educational levels and examine the role of technology integration in educator development outcomes.